One way ticket : - Bassett, Jennifer (Oxford Bookworms)
Tom Walsh had a lot to learn about life. He liked travelling, and he was in no hurry. He liked meeting people, anyone and everyone. He liked the two American girls on the train. They were nice and very friendly. They knew a lot of places. Tom thought they were fun. Tom certainly had a lot to learn about life. This is a colletion of shirt stories about adventures on trains. Strange, wonderful, and frightening things can happen on trains - and all of them happen here.